Impact of COVID-19 Pandemic on Mental Health of Health Care Workers and Its Determining Factors: A Systematic Review - Nikita Bhatta; Sangam Shah; Basanta Sharma Paudel; Sanjit Kumar Sah (Journal of Karnali Academy of Health Sciences, 2021)
Abstract